Vinyl high crystalline covalent organic framework thin films, thin film sensors, and methods of making and using the same
Patent Information
- Application Number
- CN202411187661.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-08-28
AI Technical Summary
[0007]本申请提供一种本申请属于共价有机框架材料技术领域,具体涉及一种乙烯基高结晶性共价有机框架薄膜、薄膜传感器及其制备方法和应用,旨在解决现有乙烯基COF薄膜制备工艺复杂、膜体均匀性差、不利于大规模制备的问题
[0023]本申请利用熔融聚合的方法制备均匀、厚度可控的乙烯基高结晶性共价有机框架薄膜,其工艺简单,可大规模制备;并且在制备过程中通过无溶剂合成的策略,避免了高毒性溶剂、催化剂的使用,使得材料合成更为绿色环保,降低了生产过程中的能耗,也极大的保留的COF本身孔性能,并且具备较为广泛的普适性。
Smart Images

Figure CN119039550B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of covalent organic framework materials technology, specifically relating to a vinyl highly crystalline covalent organic framework thin film, a thin film sensor, its preparation method and application. Background Technology
[0002] Covalent organic frameworks (COFs) are materials composed of light elements (H, B, C, N, O, and Si) linked by covalent bonds. Due to their ordered porous structure and customizable chemical functions, they have been extensively studied in fields such as gas storage and separation, sensing, and energy storage. Compared to other materials, COFs possess intrinsic nanopores (0.5–4.7 nm), providing molecular transport channels for efficient molecular mass transport and separation. Furthermore, COFs exhibit permanent porosity, low mass density, excellent thermal resistance, and high surface area, making them ideal for membrane applications. Since the first successful synthesis of COFs based on the condensation reaction of hexahydroxytriphenyl (HTTP) and diboronic acid (BDBA) in 2005, methods for synthesizing COFs with different structures have emerged continuously. However, articles on the preparation of COFs into membranes for molecular separation were not published until 2009, and although related research has gradually increased since then, the number remains very limited.
[0003] COF thin films can selectively identify and detect gases by inducing changes in electrical, optical, or other physical properties through specific interactions with gas molecules. By precisely controlling the pore size and chemical environment of the COF, selective adsorption and separation of gas molecules of different sizes or polarities can be achieved. For example, some functionalized COF thin films have demonstrated highly efficient detection capabilities for volatile organic compounds (VOCs) or toxic gases in environmental monitoring and industrial safety fields. Simultaneously, some COF thin films also exhibit highly selective adsorption and desorption capabilities for water vapor, providing new possibilities for applications in humidity sensors, smart packaging, and biomedical devices.
[0004] Existing methods for preparing COF thin films mainly include liquid-phase interfacial polymerization, vapor deposition, electrochemical deposition, and spin coating. Each method has its advantages and disadvantages and is suitable for different types of COF materials. For example, the reported liquid-phase interfacial polymerization method is mainly used for COFs linked by borate ester bonds (BO), imine bonds (C=N), and oxime bonds (C=N-OH). This method can prepare large-area films, but its reaction conditions are relatively strict, making it difficult to precisely control the film thickness. Vapor deposition is mainly suitable for COF monomers that are stable in the gas phase, such as imine COFs. Although it can prepare uniform films, it has strong selectivity for monomers and high equipment costs. Electrochemical deposition can precisely control the thickness and structure of the film, but it is limited to conductive substrates and electrochemically active monomers. Spin coating is suitable for pre-synthesized COF nanoparticles or COF monomers with good solubility. The process is simple and the film thickness is easy to control, but the film uniformity may be poor, especially for thicker films. Meanwhile, current research on COF thin films mainly focuses on imine bonds, oxime bonds, and hydrazide-based COF materials, while the preparation of COF material thin films with stable vinyl (C=C) linkages is still in its early stages.
[0005] Vinyl COF thin films, as stable and highly tunable crystalline porous materials, hold significant promise for applications in gas response and separation. However, due to the lack of breakthroughs in the preparation process of vinyl COF thin films, their potential for further development in gas response and separation applications remains extremely limited.
[0006] Therefore, there is an urgent need to develop a simple and easy-to-operate process for preparing vinyl COF films that is suitable for large-scale preparation, has excellent uniformity, and is easy to operate. Summary of the Invention
[0007] This application belongs to the field of covalent organic framework materials technology, specifically relating to a vinyl highly crystalline covalent organic framework thin film, a thin film sensor, its preparation method and application, aiming to solve the problems of complex preparation process, poor film uniformity and unfavorable large-scale preparation of existing vinyl COF thin films.
[0008] To achieve the above objectives, the present application adopts the following technical solution.
[0009] A first aspect of this application provides a method for preparing a vinyl-based highly crystalline covalent organic framework thin film, comprising:
[0010] S1, organic monomer A containing an active methyl functional group, organic monomer B containing an aldehyde functional group, and catalyst are mixed and heated to obtain a molten precursor;
[0011] S2, uniformly coat the molten precursor onto the substrate;
[0012] S3, the substrate is subjected to a polymerization reaction under vacuum, and the reactants are washed and dried to obtain a vinyl covalent organic framework film.
[0013] In some embodiments, the heating temperature in S1 is 80–140°C; the polymerization reaction temperature in S3 is 160–200°C, and the reaction time is 3–7 days.
[0014] In some embodiments, the organic monomer A comprises any one of 2,4,6-trimethyl-1,3,5-triazine, 2,4,6-trimethylpyridine, 2,4,6-tricyano-1,3,5-trimethylbenzene, 2,5-dimethylpyrazine, 3,6-dimethylpyridazine, 2,5-dimethylterephthalonitrile, or 2,3,5,6-tetramethylpyrazine.
[0015] In some embodiments, the organic monomer B includes 1,3,5-tris(4'-aldehyde[1,1'-biphenyl]-4-yl)benzene, 1,3,5-tris(p-formylphenyl)benzene, 4,4',4”-[benzyl-1,3,5-triyltris(acetylene-2,1-diyl)]tribenzaldehyde, 2,4,6-tris(4-aldehydephenyl)-1,3,5-triazine, 4',4”',4””'-(1,3,5-triazine-2,4,6-triyl)tris(([1,1'-biphenyl]-4-carboxaldehyde)), 2,4,6-tri- Any one of (4-formyl-biphenyl-4-yl)-1,3,5-triazine, pyromellitic methyl methacrylate, terephthalaldehyde, 1,4-bis(4-aldehyde-phenyl)benzene, 4,4'-biphenyldicarboxaldehyde, 1,2-bis(4'-formylphenyl)acetylene, 4,4'-(1,3-butyrynyl-1,4-diyl)bisbenzaldehyde, 2,5-dimethoxy-1,4-terephthalaldehyde, 4,7-bis(4-aldehyde-phenyl)benzofuran, 4,7-bis(4-aldehyde-phenyl)benzothiophene, and 4,7-bis(4-aldehyde-phenyl)benzoselenophenol.
[0016] In some embodiments, the catalyst is at least one selected from substituted or unsubstituted benzoic anhydride, sodium benzoate, benzoyl chloride, 4-trifluoromethylbenzoic anhydride, 4-methoxybenzoic anhydride, acetic anhydride, trifluoroacetic anhydride, benzoic acid, 4-fluorobenzylgallic acid, cinnamic acid, and propionic acid.
[0017] In some embodiments, the substrate is a conductive substrate or a substrate with a porous structure.
[0018] In some embodiments, the molar ratio of organic nitrogen A to organic monomer B is (1:4)-(4:1); the molar ratio of catalyst to organic monomer A is (1-8):1.
[0019] A second aspect of this application provides a vinyl highly crystalline covalent organic framework thin film prepared by the above preparation method.
[0020] A third aspect of this application provides the application of the aforementioned vinyl highly crystalline covalent organic framework thin film in gas detection, water vapor response, or gas separation.
[0021] A fourth aspect of this application provides a thin-film sensor comprising the aforementioned vinyl highly crystalline covalent organic framework thin film having a conductive substrate.
[0022] Compared with the prior art, the beneficial effects of this application are as follows:
[0023] This application utilizes melt polymerization to prepare uniform, thickness-controllable vinyl-based highly crystalline covalent organic framework films. The process is simple and can be mass-produced. Furthermore, the solvent-free synthesis strategy avoids the use of highly toxic solvents and catalysts, making the material synthesis more environmentally friendly, reducing energy consumption in the production process, greatly preserving the porosity of the COF itself, and possessing broad applicability.
[0024] The vinyl-based highly crystalline covalent organic framework thin film of this application offers broad substrate selectivity. When the substrate is an interdigitated electrode, it can be directly used as a thin-film sensor, exhibiting high sensitivity, high stability, and excellent cycling performance. The one-step film fabrication process of this application greatly simplifies the fabrication process of COFs sensors, avoiding the problems of poor contact between the material and electrode leading to defects at grain boundaries and particle interfaces, resulting in carrier mobility degradation and low sensitivity, which are often caused by defects at grain boundaries and particle interfaces in traditional material synthesis and subsequent sensor processing. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0026] Figure 1 A schematic diagram of the preparation process for vinyl-based highly crystalline covalent organic framework films;
[0027] Figure 2 The XRD pattern of a vinyl-based highly crystalline covalent organic framework thin film;
[0028] Figure 3 Infrared spectrum of a vinyl-based highly crystalline covalent organic framework thin film;
[0029] Figure 4 The adsorption-desorption curves of a vinyl-based highly crystalline covalent organic framework film under nitrogen isotherm at 77 K.
[0030] Figure 5 SEM image of a cross-section of a vinyl-based highly crystalline covalent organic framework film;
[0031] Figure 6 SEM image of the surface of a vinyl-based highly crystalline covalent organic framework film;
[0032] Figure 7 A photograph of a vinyl-based highly crystalline covalent organic framework thin film on a glass substrate;
[0033] Figure 8 Vinyl-based highly crystalline covalent organic framework films of different shapes and sizes;
[0034] Figure 9 The graph shows the response-recovery curve of the thin-film sensor to SO2 at room temperature.
[0035] Figure 10 The graph shows the electrical signal response of the thin-film sensor to different concentrations of SO2 gas.
[0036] Figure 11 The graph shows the response performance of the thin-film sensor to different concentrations of SO2 gas over 5 cycles.
[0037] Figure 12 This is a stability curve of the thin-film sensor for detecting SO2 gas at different concentrations. Detailed Implementation
[0038] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0039] In the following description of this embodiment, the terms "including", "comprising", "having", and "containing" are all open-ended terms, meaning that they include but are not limited to.
[0040] In the following description of this embodiment, the term "and / or" is used to describe the association relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, B existing alone, and A and B existing simultaneously. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0041] In the following description of this embodiment, the term "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0042] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms "a" and "the" as used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0043] Those skilled in the art should understand that, in the following description of the embodiments of this application, the sequence of numbers does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0044] Those skilled in the art will understand that the numerical ranges in the embodiments of this application should be understood as each intermediate value between the upper and lower limits of the specifically disclosed range. Each smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this application. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0045] Unless otherwise stated, the technical / scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. While this application describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this application. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0046] In a first aspect, this application provides a method for preparing a vinyl highly crystalline covalent organic framework thin film. Figure 1 This is a schematic diagram of the process flow of this application, such as... Figure 1 As shown, this application does not require solvents and employs an in-situ growth and coating method. The catalyst, organic monomer A, and organic monomer B are heated to a molten state, then uniformly coated onto any substrate. Finally, the molten precursor coated on the substrate is polymerized at high temperature to obtain a covalent organic framework material film. Specifically, it includes:
[0047] S1, an organic monomer A containing an active methyl functional group, an organic monomer B containing an aldehyde functional group, and a catalyst are mixed and heated to obtain a molten precursor;
[0048] Specifically, organic monomer A containing an active methyl functional group, organic monomer B containing an aldehyde functional group, and a catalyst are added to a container and heated to 80–140°C to melt the mixture. The melting time is preferably 0.5–48 h to obtain the precursor. The catalyst serves two purposes: firstly, it lowers the melting point of organic monomer B containing the aldehyde functional group, causing it to melt at a lower temperature and mix uniformly with organic monomer A containing the active methyl functional group, which is beneficial for coating; secondly, the catalyst catalyzes the polymerization of organic monomer A and organic monomer B under high-temperature conditions in subsequent steps to generate a vinyl COF material. The catalyst is selected from compounds containing anhydride functional groups, acyl chloride functional groups, or carboxylic acid functional groups.
[0049] S2, uniformly coat the molten precursor onto the substrate;
[0050] Specifically, a molten precursor film is formed on the surface of a substrate by coating a molten precursor onto the substrate surface. During the film formation process, the film coating thickness and size, as well as the material and shape of the substrate, can be adjusted arbitrarily, providing great flexibility. In the embodiments of this application, the preferred film coating thickness is 1-50 micrometers.
[0051] The substrate material of this application is not limited. Depending on the application of the vinyl highly crystalline covalent organic framework film, the substrate may be a conductor, such as interdigitated electrodes, conductive glass, metal mesh or metal sheet; a porous material, such as porous ceramic; or ordinary glass.
[0052] S3, the substrate is subjected to a polymerization reaction under vacuum, and the reactants are washed and dried to obtain a vinyl covalent organic framework film;
[0053] The substrate coated with the molten precursor is placed in a reactor, evacuated to a pressure less than 1 atm, and heated to 160–200°C for polymerization. The reaction time is 3–7 days, resulting in the in-situ formation of vinyl-linked COF films. The reactor can be a high-temperature and high-pressure resistant Pyrex tube, a flame-sealed ampoule, a high-pressure reactor, or a vacuum high-temperature oven.
[0054] The film obtained after polymerization was washed with DMF to remove unreacted monomers, and then washed with CH3OH to remove residual catalyst. Subsequently, the film was soaked in anhydrous tetrahydrofuran solvent for 12 h to remove unreacted small molecules in the film channels. Finally, the obtained COF film was dried in a vacuum drying oven at 100 °C for 12 h to obtain a vinyl highly crystalline covalent organic framework film.
[0055] This application presents a one-step method for preparing large-area and uniform vinyl-linked COFs thin films, which offers advantages such as controllable thickness, adjustable shape, and variable substrate. The process is simple and can be mass-produced. Furthermore, the solvent-free synthesis strategy avoids the use of highly toxic solvents and catalysts, making the material synthesis more environmentally friendly, reducing energy consumption in the production process, and greatly preserving the porosity of the COFs, with pore sizes ranging from 0.5 to 5.0 nm.
[0056] In this application, the organic monomer A contains an active methyl functional group, including any one of 2,4,6-trimethyl-1,3,5-triazine, 2,4,6-trimethylpyridine, 2,4,6-tricyano-1,3,5-trimethylbenzene, 2,5-dimethylpyrazine, 3,6-dimethylpyridazine, 2,5-dimethylterephthalonitrile, or 2,3,5,6-tetramethylpyrazine.
[0057] The organic monomer B contains an aldehyde functional group, including 1,3,5-tris(4'-aldehyde[1,1'-biphenyl]-4-yl)benzene, 1,3,5-tris(p-formylphenyl)benzene, 4,4',4”-[benzene-1,3,5-triyltris(acetylene-2,1-diyl)]tribenzaldehyde, 2,4,6-tris(4-aldehydephenyl)-1,3,5-triazine, 4',4”',4””'-(1,3,5-triazine-2,4,6-triyl)tris(([1,1'-biphenyl]-4-carboxaldehyde)), 2,4,6-tri- Any one of (4-formyl-biphenyl-4-yl)-1,3,5-triazine, pyromellitic methyl methacrylate, terephthalaldehyde, 1,4-bis(4-aldehyde-phenyl)benzene, 4,4'-biphenyldicarboxaldehyde, 1,2-bis(4'-formylphenyl)acetylene, 4,4'-(1,3-butyrynyl-1,4-diyl)bisbenzaldehyde, 2,5-dimethoxy-1,4-terephthalaldehyde, 4,7-bis(4-aldehyde-phenyl)benzofuran, 4,7-bis(4-aldehyde-phenyl)benzothiophene, and 4,7-bis(4-aldehyde-phenyl)benzoselenophenol.
[0058] The catalyst is a compound containing an anhydride functional group, a compound containing an acyl chloride functional group, or a compound containing a carboxylic acid functional group. It may be at least one of substituted or unsubstituted benzoic anhydride, sodium benzoate, benzoyl chloride, 4-trifluoromethylbenzoic anhydride, 4-methoxybenzoic anhydride, acetic anhydride, trifluoroacetic anhydride, benzoic acid, 4-fluorobenzylgallic acid, cinnamic acid, and propionic acid.
[0059] In this application, the molar ratio of organic monomer A to organic monomer B is (1:4)-(4:1), preferably 1:(1-2); the molar ratio of catalyst to organic monomer A is (1-8):1, preferably (1-4):1. Within this ratio range, it is beneficial to prepare a uniform vinyl highly crystalline covalent organic framework film.
[0060] The vinyl-based highly crystalline covalent organic framework thin film prepared in this application is uniform, has controllable thickness, adjustable shape, and variable substrate, showing broad application prospects. Through specific interactions with gas molecules, it can induce changes in electrical, optical, or other physical properties, thereby achieving selective identification and detection of gases. Its substrate has broad selectivity; when the substrate is a conductive material, such as interdigitated electrodes, metal mesh, metal sheet, or conductive glass, the prepared vinyl-based highly crystalline covalent organic framework thin film exhibits electro-signal responsiveness. The vinyl-based highly crystalline covalent organic framework thin film prepared in this application can be used as a sensor in the fields of gas adsorption detection, water vapor response, and gas separation.
[0061] Furthermore, this application uses a conductive material substrate to prepare a vinyl highly crystalline covalent organic framework thin film, which greatly simplifies the fabrication process of COFs sensors. It avoids the problems of poor contact between the material and the electrode in the traditional process of synthesizing materials and then processing them into sensors, which leads to defects between grain boundaries and particle interfaces, resulting in carrier mobility degradation and low sensitivity.
[0062] This application provides a thin-film sensor comprising a vinyl-based highly crystalline covalent organic framework thin film prepared using interdigitated electrodes as a substrate. The thin-film sensor can respond to low concentrations of SO2, VOCs, or water vapor. Specifically, when the thin-film sensor comes into contact with low concentrations of SO2 or VOCs, an electrical signal change occurs, such as a change in resistance, voltage, current, or capacitance; when the thin-film sensor comes into contact with water vapor, structural bending occurs. Based on the electrical signal change or structural bending value, low concentrations of SO2, VOCs, or water vapor can be detected. The VOC gas can be any one of NH3, SO2, or toluene.
[0063] For example, a vinyl-based highly crystalline covalent organic framework thin film is prepared using the interdigitated electrode as a substrate and placed in a sealed chamber. At a fixed temperature, different volumes of SO2 are injected into the chamber, and the changes in the electrical signal of the thin film in response to different concentrations of SO2 gas are recorded using an LCR bridge, thereby realizing the detection of SO2 gas.
[0064] The present application will be further illustrated by the following examples.
[0065] Example 1
[0066] This application provides a method for preparing a vinyl-based highly crystalline covalent organic framework thin film.
[0067] Weigh 0.2 mmol of 2,4,6-trimethyl-1,3,5-triazine, 0.2 mmol of pyromellitic methyl ester, and 0.4 mmol of benzoic anhydride, place them in a glass bottle, and heat at 100 °C for 2 h to obtain a molten precursor.
[0068] A molten precursor was coated onto an interdigitated electrode using an automated coating machine to form a molten precursor film with a thickness of 5 micrometers. The interdigitated electrode coated with the molten precursor was then placed in a furnace with a vacuum of 0.15 mmHg and heated at 180°C for 120 h. The prepared film was then cleaned with DMF and methanol, respectively, and immersed in anhydrous tetrahydrofuran for 12 h, followed by drying at 100°C for 12 h to obtain a vinyl-based highly crystalline covalent organic framework film.
[0069] Example 2
[0070] This application provides a method for preparing a vinyl-based highly crystalline covalent organic framework thin film.
[0071] Weigh 0.1 mmol of 2,4,6-trimethyl-1,3,5-triazine, 0.4 mmol of pyromellitic tricarboxaldehyde, and 0.8 mmol of benzoic anhydride, place them in a glass bottle, and heat at 100 °C for 2 h to obtain a molten precursor.
[0072] A molten precursor was coated onto an interdigitated electrode using an automated coating machine to form a molten precursor film with a thickness of 12 micrometers. The interdigitated electrode coated with the molten precursor was then placed in a furnace with a vacuum of 0.15 mmHg and heated at 180°C for 120 h. The prepared film was then cleaned with DMF and methanol, respectively, and immersed in anhydrous tetrahydrofuran for 12 h, followed by drying at 100°C for 12 h to obtain a vinyl-based highly crystalline covalent organic framework film.
[0073] Example 3
[0074] This application provides a method for preparing a vinyl-based highly crystalline covalent organic framework thin film.
[0075] Weigh 0.4 mmol of 2,4,6-trimethyl-1,3,5-triazine, 0.1 mmol of pyromellitic methyl ester, and 0.4 mmol of benzoic anhydride, place them in a glass bottle, and heat at 100 °C for 2 h to obtain a molten precursor.
[0076] A molten precursor was coated onto an interdigitated electrode using an automated coating machine to form a molten precursor film with a thickness of 21 micrometers. The interdigitated electrode coated with the molten precursor was then placed in a furnace with a vacuum of 0.15 mmHg and heated at 180°C for 120 h. The prepared film was then cleaned with DMF and methanol, immersed in anhydrous tetrahydrofuran for 12 h, and subsequently dried at 100°C for 12 h to obtain a vinyl-based highly crystalline covalent organic framework film.
[0077] Example 4
[0078] The difference between Example 4 and Example 1 is that 2,4,6-trimethyl-1,3,5-triazine is replaced with 2,4,6-trimethylpyridine, and the coating thickness of the molten precursor on the interdigitated electrode is 27 micrometers. All other aspects are the same as in Example 1.
[0079] Example 5
[0080] The difference between Example 5 and Example 1 is that pyromellitic methyl ester is replaced with 1,3,5-tris(4'-aldehyde[1,1'-biphenyl]-4-yl)benzene, and all other aspects are the same as in Example 1.
[0081] Example 6
[0082] The difference between Example 7 and Example 1 is that the interdigitated electrodes are replaced with glass, while the rest are the same as in Example 1.
[0083] The performance of the vinyl highly crystalline covalent organic framework thin film prepared in Example 1 was tested, including XRD, infrared spectroscopy, SEM, and isothermal adsorption-desorption tests.
[0084] Figure 2 Its XRD pattern. From Figure 2 It is known that vinyl highly crystalline covalent organic framework films have very high crystallinity.
[0085] Figure 3 The infrared spectrum of the film confirmed that the film prepared in Example 1 was a vinyl-linked COF material, with a 1626 cm⁻¹... -1 The peak corresponds to the stretching vibration of a carbon-carbon double bond.
[0086] Figure 4 The nitrogen isotherm adsorption-desorption curve at 77K shows that its BET surface area is 536 m². 2 / g, with a pore size of 0.58nm, has a large specific surface area and a small pore size.
[0087] Figure 5 The images show SEM images of cross-sections of vinyl-based highly crystalline covalent organic framework films with different coating thicknesses prepared in Examples 1-4. The top left image is Example 1, the top right image is Example 2, the bottom left image is Example 3, and the bottom right image is Example 4. The thicknesses range from 5 to 30 μm.
[0088] Figure 6 The images show SEM images of the vinyl-based highly crystalline covalent organic framework film prepared in Example 1. The top left image shows the uncoated blank substrate, and the top right image shows the vinyl-based highly crystalline covalent organic framework film. The bottom left and bottom right images are magnified views of the vinyl-based highly crystalline covalent organic framework film at different scales. Figure 6 It can be seen that the vinyl highly crystalline covalent organic framework film is grown in situ on the substrate surface and has very good uniformity.
[0089] Figure 7 The image shows a physical picture of the vinyl-based highly crystalline covalent organic framework film prepared in Example 7. Its size can reach about 10 cm, which can be prepared on a large scale.
[0090] Depending on the shape and size of the substrate, this application can prepare vinyl-based highly crystalline covalent organic framework films of different shapes and sizes, such as... Figure 8 As shown.
[0091] The vinyl-based highly crystalline covalent organic framework thin film of the interdigitated electrode substrate prepared in Example 1 was used as a thin-film sensor for performance evaluation, including:
[0092] 1. SO2 detection experiment, the specific method is as follows:
[0093] The thin-film sensor was placed in a test chamber equipped with a temperature control device, and connected to an LCR instrument using a clamp to detect changes in the electrical signal. During the experiment, the test chamber was first purged with air to remove any remaining substances until baseline equilibrium was reached. Then, a certain volume of SO2 was injected using a micro-syringe to test the thin-film sensor's sensing performance for low concentrations of SO2.
[0094] Figure 9 The graph shows the response-recovery behavior of the thin-film sensor to SO2 at room temperature. The response time is approximately 3.47 min and the recovery time is approximately 4.03 min.
[0095] Figure 10 The graph shows the response behavior of the thin-film sensor in the SO2 concentration range of 1 to 1000 ppm. The vertical axis represents the rate of change of capacitance, and the horizontal axis represents time. Figure 10This indicates that the thin-film sensor has a response signal to the concentration gradient of SO2. By calculating the root mean square deviation, the detection limit of the thin-film sensor can be obtained as 86 ppb.
[0096] 2. Cyclic Response Test
[0097] The thin-film sensor was subjected to cyclic stability tests at room temperature with SO2 concentrations ranging from 1 to 1000 ppm. After each test, the sensor was purged with nitrogen for recovery. The results are as follows: Figure 11 As shown.
[0098] Figure 11 The vertical axis represents the rate of change of capacitance, and the horizontal axis represents time. Figure 11 This indicates that the sensor film maintains a stable and consistent detection level over at least 5 cycles, demonstrating excellent stability.
[0099] 3. Stability testing
[0100] The thin-film sensor was subjected to a two-month cyclic test under SO2 concentrations of 20 ppm, 115 ppm, 225 ppm, and 1000 ppm. The test results are as follows: Figure 12 As shown, the vertical axis represents the capacitance change rate, and the horizontal axis represents time, demonstrating the high stability and repeatability of the thin-film sensor under different concentration cycles.
[0101] The test results above demonstrate that the thin-film sensor of this application exhibits high sensitivity, high stability, and excellent cycling performance. It effectively solves the problems of poor contact between the material and the electrode in traditional sensor fabrication processes, which leads to defects at grain boundaries and particle interfaces, resulting in degraded carrier mobility and low sensitivity.
[0102] Although this application has been described in detail in this specification with general descriptions and specific embodiments, some modifications or improvements can be made to it, which will be obvious to those skilled in the art. Therefore, such modifications or improvements made without departing from the spirit of this application are all within the scope of protection claimed in this application.
Claims
1. A method for preparing a vinyl-based highly crystalline covalent organic framework thin film, characterized in that, include: S1, organic monomer A containing an active methyl functional group, organic monomer B containing an aldehyde functional group, and catalyst are mixed and heated to obtain a molten precursor; S2, uniformly coat the molten precursor onto the substrate; S3, the substrate is subjected to a polymerization reaction under vacuum, and the reactants are washed and dried to obtain a vinyl covalent organic framework film; The heating temperature described in S1 is 80 ~ 140 ℃; The polymerization reaction described in S3 is carried out at a temperature of 160~200 ℃ for 3-7 days. The vacuum level is 0.15 mmHg; The organic monomer A comprises 2, 4, 6 Trimethyl 1, 3, 5 Triazine, 2,4,6 Trimethylpyridine, 2,4,6 Tricyano 1, 3, 5 Trimethylbenzene, 2,5-dimethylbenzene Dimethylpyrazine, 3,6 Dimethylpyridazine, 2,5 Dimethylterephthalonitrile or 2,3,5,6 Any one of tetramethylpyrazine; The organic monomer B includes 1, 3, 5 Three (4') Aldehyde group [1,1'] [Biphenyl] 4 (Base)benzene, 1,3,5 Tris(p-formylphenyl)benzene, 4,4',4'' [benzene 1, 3, 5 Three-base-three (acetylene) twenty one [2,4,6]tribenzaldehyde, 2,4,6 3(4) Aldehyde phenyl) 1, 3, 5 Triazine, 4',4''',4''''' (1,3,5) Triazine 2,4,6 Three basics) Three (([1 ,1 ' [Biphenyl] 4 Formaldehyde), 2,4,6 three (4 formyl group Biphenyl 4 base) 1, 3, 5 Triazine, pyromellitic methyl methacrylate, terephthalaldehyde, 1,4- 2(4) Aldehyde-phenyl)benzene, 4,4' Biphenyl dimethylformaldehyde, 1,2 2 (4') (formylphenyl)acetylene, 4,4' (1,3) Butyryl 1,4 Dimethylbenzaldehyde, 2,5-diphenylformaldehyde Dimethoxy 1,4 terephthalaldehyde, 4,7 2(4) Aldehyde-phenyl)benzofuran, 4,7 2(4) Aldehyde-phenyl)benzothiophene, 4,7 2(4) Any one of (aldehyde-phenyl)benzoselenol.
2. The preparation method according to claim 1, characterized in that, The catalyst is at least one of substituted or unsubstituted benzoic anhydride, sodium benzoate, benzoyl chloride, 4-trifluoromethylbenzoic anhydride, 4-methoxybenzoic anhydride, acetic anhydride, trifluoroacetic anhydride, benzoic acid, 4-fluorobenzylgallic acid, cinnamic acid, and propionic acid.
3. The preparation method according to claim 1, characterized in that, The substrate is a conductive substrate or a substrate with a porous structure.
4. The preparation method according to claim 1, characterized in that, The molar ratio of organic monomer A to organic monomer B is (1:4)-(4:1); the molar ratio of catalyst to organic monomer A is (1-8):
1.
5. A vinyl highly crystalline covalent organic framework film prepared by the preparation method according to any one of claims 1-4.
6. The application of the vinyl highly crystalline covalent organic framework thin film of claim 5 in gas detection, water vapor response, or gas separation.
7. A thin-film sensor, characterized in that, Including the vinyl highly crystalline covalent organic framework film as described in claim 5.
Citation Information
Patent Citations
Solvent-free method for rapidly preparing covalent organic framework material and membrane block material thereof in macroscopic mode
CN118515833A